2014
DOI: 10.1016/j.jtcvs.2014.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Event recorder monitoring to compare the efficacy of a left versus biatrial lesion set in patients undergoing concomitant surgical ablation for atrial fibrillation

Abstract: Continuous rhythm monitoring by subcutaneous event recorder implantation was safe and feasible. In patients undergoing biatrial ablation, a statistically significant higher rate of freedom from atrial fibrillation was observed at 12 months follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…In the same study, ablation was associated with an increased risk of implantation of a permanent pacemaker, but authors didn't study the difference between the two lesion sets. In the other hand, Pecha et al [13] in a recent study using the same device employed in our study, a statistically significant higher rate of freedom from atrial fibrillation was observed in patients with a biatrial lesion with lower AF burden. However, they reported a double rate of postoperative pacemaker in patients with biatrial lesion.…”
Section: Discussionsupporting
confidence: 47%
“…In the same study, ablation was associated with an increased risk of implantation of a permanent pacemaker, but authors didn't study the difference between the two lesion sets. In the other hand, Pecha et al [13] in a recent study using the same device employed in our study, a statistically significant higher rate of freedom from atrial fibrillation was observed in patients with a biatrial lesion with lower AF burden. However, they reported a double rate of postoperative pacemaker in patients with biatrial lesion.…”
Section: Discussionsupporting
confidence: 47%
“…In a previous published study by our group [23], including only patients with persistent AF, we showed higher rate of freedom from AF in patients receiving biatrial lesion set, compared to those with left atrial lesion set only. We did not find these differences in the present study; however, it has to be admitted that in this study also patients with paroxysmal AF were included.…”
Section: Discussionsupporting
confidence: 45%
“…After years of different ablation techniques and lesion sets being tried in concomitant AF operations, evidence supports a biatrial lesion set mimicking the CM-III incisional pattern as the optimal treatment [10,18,19]. At present, most surgeons perform biatrial procedures with linear surgical ablation with radiofrequency or cryoablation.…”
Section: Commentmentioning
confidence: 99%